Application of the Rasch measurement model in rehabilitation research and practice: early developments, current practice, and future challenges - Tennant, Alan; Küçükdeveci, Ayse A. (Frontiers in Rehabilitation Sciences, 2023)
The application of the Rasch measurement model in rehabilitation is now well established. Both its dichotomous and polytomous forms provide for transforming ordinal scales into interval-level measures, consistent with the requirements of fundamental measurement. The growth of applying the model in rehabilitation spans 30 years, during which both the protocol has steadily developed and several software packages have emerged that provide for analysis, together with the “R” language that has an increasing set of codes for applying the model. This article reviews that development and highlights current practice requirements, including those for providing the relevant information for the methods, and what is expected of the analysis. In addition, this provides a worked example and looks at the remaining issues and current developments of its application.